Conceptual formation of a system-integrated organizational and technological model of energy-efficient construction - HALUSHKO, Dmytro (Ways to Improve Construction Efficiency, 2025)
The article considers the conceptual foundations of the formation of a system-integrated organizational and technological model of energy-efficient construction, taking into account energy-saving technological solutions. The relevance of the study is due to the need to increase the efficiency of energy use in the construction industry, which is one of the largest consumers of energy. In the context of rising energy costs, strengthening environmental requirements and the transition to sustainable development, it is especially important to form scientifically based models that provide comprehensive management of energy costs at all stages of construction. In the course of the analysis of research and publications, it was found that a significant number of scientific works, in particular by teachers of the Kyiv National University of Civil Engineering and Architecture, are devoted to certain aspects of energy efficiency – technological, material or organizational. However, the issue of systemic integration of these aspects into a single managed model remains insufficiently developed. Domestic and foreign authors emphasize the need to create multi-level management systems capable of ensuring the optimization of processes based on energy-saving technologies. The scientific significance of the work lies in the development of a conceptual scheme of a system-integrated organizational and technological model that combines the principles of energy efficiency, technological controllability and rational resource provision. This approach contributes to the improvement of the theoretical foundations of construction organization, expands the idea of intersystem relationships between technological and organizational components, forms prerequisites for the creation of complex models of construction process management. The practical significance of the results obtained lies in the possibility of applying the developed conceptual provisions in the planning, organization and control of construction and installation works. The proposed model can be used to improve the energy efficiency of construction enterprises, optimize production resources, reduce energy consumption and increase the economic efficiency of construction projects. The introduction of a system-integrated approach ensures an improvement in the quality of construction, a reduction in the time of work and the creation of a modern energy-saving environment.